Controllable ZnO architectures synthesised on zinc substrates by hydrothermal preparation for enhanced photocatalytic activity. (April 2014) - Guo, W. R.; Zhao, X. R.; Zhang, Y. X.; Duan, L. B.; Guan, M. M.; Cao, M. M.; Liu, J. R.; Wang, Y. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Controllable ZnO architectures have been achieved on zinc substrates via a versatile one-pot hydrothermal method without assistance of any surfactants or organic solvent. The morphologies of ZnO architectures have been successfully manipulated by adjusting the concentration of NaOH and temperature of the reaction system. Among the as prepared ZnO architectures, the sheet flower-like ones exhibited highest photocatalytic activity in the degradation of methyl orange (MO) under ultraviolet (UV) illumination for their nanosheets assembled structural feature.